Equation for fitting dispersed systems gravity and centrifuge settling data - Mota, M. (2008)
Liquid phase accumulation kinetics during sedimentation and centrifugation serves as a source of information about the average settling properties of dispersed systems. A power order fitting function is proposed for describing the dependence of accumulated liquid phase volume on settling time. The function validity was tested for numerous experimental settling data under gravitational and centrifugal forces for different dispersed systems. The obtained results give good correlation between experimental data and fitting curves even when settling displays a lag period. The main advantage of the proposed model is the possibility to fit the liquid phase accumulation kinetics in a wide range of settling time and solids concentration. The power order fitting function allows simulating the liquid phase accumulation in the case of limited experimental data.